Transcendental Method for Research with Human Subjects: A Transformative Phenomenology for the Human Sciences. Issue 3 (August 2013) - Perry, Donna J.
This article provides an overview of a qualitative research method called transcendental method for research with human subjects. The method employs a transformative phenomenological approach and was developed using the philosophy of Bernard Lonergan. Reflective use of this method suggests that it has both investigational and interventional qualities, with transformative potential for both researcher and study participants.